An optimized hybrid rocket motor for the SARA platform reentry system - Cás, Pedro Luiz Kaled Da (2012)
This paper has described a system design process, based on a multidisciplinary optimization technique, of a conceptual optimized hybrid propellant rocket motor. The proposed engine could be a technological option for the reentry maneuvering system of the Brazilian recoverable satellite (SARA), which was designed by the Brazilian Institute of Aeronautics and Space. The resulting optimized propulsion system must be viewed as a proof of concept allowing comparison to more conventional technologies, i.e., liquid and solid motors. Design effort was conducted for hybrid propellants engines based on a liquefying fuel (solid paraffin) and two different oxidizers, H2O2 (90% high-testperoxide) and self-pressurizing N2O. The multidisciplinary configuration optimization technique was supported on geometrical operating parameters of the motor, rather than on performance, in order to facilitate subsequent design and fabrication. Results from the code presented a hybrid motor, which was considered a competitive alternative for the deboost engine when compared to the traditional chemical systems, solid and liquid bipropellant, and monopropellant. The estimated mass of the reentry system, for the cases addressed in this study, varied from 22 to 29 kg, which is lower than either liquid bipropellant or solid engines formerly proposed.